KARAKTERISTIK BAHASA JAWA DIALEK JAWA TIMUR oleh Maryaeni Fakultas Sastra Universitas Malang Abstract The Javanese spoken by its speech communities in East Java has characteristics different from those of the Javanese spoken by its speech communities in o - -, Maryaeni (Diksi, 2006)
The Javanese spoken by its speech communities in East Java hascharacteristics different from those of the Javanese spoken by its speechcommunities in other regions of Java. The characteristics can be examined in termsof its word form and word choice in everyday utterances made by its speakers. Thedifferences become more marked when one relates the utterances with the socialclassbackground of the speakers. Based on its characteristics, the Javanese in EastJava can geographically be called the Javanese East Java dialect.Keywords: characteristics, East Java dialect